The Application of Project-Based Learning with Constructivism Theory in Enhancing Creativity of Elementary School Students: A Literature Review - Milla, Daindo (Journal La Edusci, 2025)
The age of twenty-first century demands the development of creative abilities that begins during childhood. Project-Based Learning (PBL) which derives from constructivist theory functions as an efficient method to develop creativity in elementary school environments. Researchers have conducted an organized review of scholarly works that analyze how PBL influences creativity development through evaluation of fluency and flexibility together with originality and elaboration. The research indicates PBL enables students to become autonomous while engaging them and collaborating with peers which leads them to acquire creative problem-solving skills applicable to actual scenarios. The extensive use of PBL faces various obstacles that prevent its full implementation. The main barriers to PBL's implementation include restricted time availability and insufficient teacher capacity and lack of resources and inadequate assessment systems for creativity. Lack of schooling for PBL implementation exists among numerous instructors while rigid curricular frameworks usually constrain project-based methods. The inability of traditional assessment methods to accurately determine creativity creates boundaries in measuring long-term effects. The complete implementation of PBL in elementary education requires policy revision combined with teacher training programs and different assessment approaches specific for creative learning. These challenges need proper resolution so PBL can establish classrooms as student-engaging learning spaces for developing students who succeed in school and work. Future research about PBL demands extensive investigations of its enduring creativity effects together with effective methods to enlarge its application across different educational environments.